IMPLEMENTATION OF TOURISM VILLAGE POLICY IN AGUSEN VILLAGE, GAYO LUES REGENCY - Sufi Sufi; Lisa Iryani (RADJA PUBLIKA, 2022)
This study aims to describe the implementation of the Qanun policy of Gayo Lues Regency Number 4 of 2016 concerning tourism, one of its contents is about the development, management and services of tourism that must be developed. One of them is the Agusen tourist village, which is located in Agusen village, Blangkejeren sub-district, the development which is still not optimal is a serious problem for the Gayo Lues district government to develop this Agusen tourist village. As for the focus of research from the implementation of local government policies regarding the Agusen tourism village, it focuses on communication, resources, disposition of implementers, bureaucratic structure and obstacles faced by local governments in the development and development of the Agusen tourism village object. This research uses qualitative methods using data collection techniques by observation, interviews and documentation. From the results of the study, it can be concluded that the communication that exists between the Gayo Lues district tourism office and the Agusen village government is going well, but the communication carried out with the Agusen village community does not go as desired, the implementation resources in development and development involve several related parties such as the local government agency. tourism in the Gayo Lues district, the Agusen village government, visitors, and the Agusen village community, the obstacles faced from the implementation of this policy are the lack of public awareness of the importance of developing this Agusen tourist village, and the lack of budget to develop and build this tourism object. The suggestion is that the local government and the Agusen village community work together to develop this Agusen tourist village both in terms of infrastructure, services and human resources.